Antibiofilm Activity of Antarctic Sponge-Associated Bacteria against Pseudomonas aeruginosa and Staphylococcus aureus - Carmen Rizzo; Vincenzo Zammuto; Angelina Lo Giudice; Maria Giovanna Rizzo; Antonio Spanò; Pasqualina Laganà; Miguel Martinez; Salvatore Guglielmino; Concetta Gugliandolo (Journal of Marine Science and Engineering, 2021)
Bioprospecting in unusual marine environments provides an innovative approach to search novel biomolecules with antibiofilm activity. Antarctic sponge-associated bacteria belonging to Colwellia, Pseudoalteromonas, Shewanella and Winogradskyella genera were evaluated for their ability to contrast the biofilm formation by Pseudomonas aeruginosa ATCC 27853 and Staphylococcus aureus ATCC 29213, as model organisms. All strains were able to produce biofilm at both 4 and 25 °C, with the highest production being for Colwellia, Shewanella and Winogradskyella strains at 4 °C after 24 h. Antibiofilm activity of cell-free supernatants (CFSs) differed among strains and on the basis of their incubation temperature (CFSs4°C and CFSs25°C). The major activity was observed by CFSs4°C against S. aureus and CFSs25°C against P. aeruginosa, without demonstrating a bactericidal effect on their growth. Furthermore, the antibiofilm activity of crude extracts from Colwellia sp. GW185, Shewanella sp. CAL606, and Winogradskyella sp. CAL396 was also evaluated and visualized by confocal laser scanning microscopic images. Results based on the surface-coating assay and surface tension measurements suggest that CFSs and the crude extracts may act as biosurfactants inhibiting the first adhesion of P. aeruginosa and S. aureus. The CFSs and the novel biopolymers may be useful in applicative perspectives for pharmaceutical and environmental purposes.